Retrievals of the Far Infrared Surface Emissivity Over the Greenland Plateau Using the Tropospheric Airborne Fourier Transform Spectrometer (TAFTS). Issue 22 (22nd November 2017) - Bellisario, Christophe; Brindley, Helen E.; Murray, Jonathan E.; Last, Alan; Pickering, Juliet; Harlow, R. Chawn; Fox, Stuart; Fox, Cathryn; Newman, Stuart M.; Smith, Maureen; Anderson, Doug; Huang, Xianglei; et al.
Abstract: The Tropospheric Airborne Fourier Transform Spectrometer measured near surface upwelling and downwelling radiances within the far infrared (FIR) over Greenland during two flights in March 2015. Here we exploit observations from one of these flights to provide in situ estimates of FIR surface emissivity, encompassing the range 80–535 cm −1 . The flight campaign and instrumental setup are described as well as the retrieval method, including the quality control performed on the observations. The combination of measurement and atmospheric profile uncertainties means that the retrieved surface emissivity has the smallest estimated error over the range 360–535 cm −1 (18.7–27.8 μm), lying between 0.89 and 1 with an associated error that is of the order ±0.06. Between 80 and 360 cm −1, the increasing opacity of the atmosphere, coupled with the uncertainty in the atmospheric state, means that the associated errors are larger and the emissivity values cannot be said to be distinct from 1. These FIR surface emissivity values are, to the best of our knowledge, the first ever from aircraft‐based measurements. We have compared them to a recently developed theoretical database designed to predict the infrared surface emissivity of frozen surfaces. When considering the FIR alone, we are able to match the retrievals within uncertainties. However, when we include contemporaneous retrievals from the mid‐infrared (MIR), no single theoretical representation is able to capture the FIR and MIR behaviors simultaneously. Our results point toward the need for model improvement and further testing, ideally including in situ characterization of the underlying surface conditions. Key Points: Retrievals of far infrared surface emissivity are reported for the first time, exploiting aircraft observations taken over Greenland The retrieved emissivity reaches values as low as 0.89 over the range 360–535 cm −1, where the associated uncertainties are smallest Simulations of the surface emissivity are unable to simultaneously match retrievals in the far and mid‐infrared